Is there a relationship between socioeconomic factors and prevalence, adherence and outcome in childhood epilepsy? A systematic scoping review. (May 2022) - Huber, Rehana; Weber, Peter
Abstract: Objectives: Socioeconomic factors play a role in the outcome of chronic diseases in childhood. Epilepsy is the most common chronic neurological disease in childhood. The relationship between socioeconomic factors and prevalence, adherence and outcome in children with epilepsy has not been systematically reviewed and therefore the aim of our study. Methods: Searches were conducted in PubMed, Embase and Cochrane databases from the first documented publications until 31st May 2020. The keywords included socioeconomic status, epilepsy, anticonvulsant, children and systematic review. Results: The search generated 4687 abstracts. 26 articles were included in the final analysis after the screening process. We found one paper regarding prevalence, 12 regarding adherence and 13 regarding outcome and their relationship to socioeconomic factors. Socioeconomic factors of caregivers impacted school performance, seizure freedom, quality of life and risk of unemployment in adulthood. Lower socioeconomic status was associated with non-adherence. Epilepsy may be more prevalent in children living in lower socioeconomic neighborhoods. Conclusion: Socioeconomic factors of the caregiver, especially their level of education, annual income and marital status, had a significant impact on the outcome and adherence to anticonvulsants in children with epilepsy. Children belonging to a lower socioeconomic group are at risk of having poorer outcomes regarding adherence and hence remission, quality of life and academic achievement. We need to recognize this important aspect and take it into account when making a treatment plan for children with epilepsy. Highlights: ⁃ The article analyses the existing medical literature about the association between socioeconomic status of epileptic children and its influence on prevalence, adherence and outcome. ⁃ The paper establishes a clear relationship between low socioeconomic status and non-adherence as well as outcome in children with epilepsy. ⁃ This review article helps to provide a better overall assessment and management for children with epilepsy.